Comparative evaluation of equine mesenchymal stem cells derived from amniotic fluid and umbilical cord blood - GULATI, BALDEV R; KUMAR, RAJESH; MOHANTY, NIHARIKA; GERA, SANDEEP; KUMAR, PAWAN; YADAV, PREM S (The Indian Journal of Animal Sciences, 2016)
Mesenchymal stem cells (MSCs) are promising therapeutic tools for the treatment of tendon rupture and other musculoskeletal injuries in horses. Although MSCs from bone marrow and adipose tissues are commonly used for therapeutic purpose in equines, umbilical cord blood (UCB) and amniotic fluid (AF) are potential non-invasive sources of MSCs. We collected AF and UCB from twenty mares during foaling for isolation of MSCs and evaluated them for the differences in isolation rates, proliferation capacity, expression of MSC markers and multi-lineage differentiation ability. The plastic adherent colonies were observed in 60% AF and 65% UCB samples. The mean doubling time for AF cells was significantly lower than that of UCB cells. The AF-MSCs proliferated till passage 36 whereas UCB-MSCs till passage 20 only. Both AF and UCB derived cells expressed CD29, CD44, CD73, CD90 and CD105 and were negative for haematopoietic and leukocytic markers (CD14, CD34 and CD45). The CD90 and CD73 expression was significantly higher in AF derived cells as compared to UCB-MSCs. On the other hand, CD29 expression was significantly lower in AF derived cells as compared to UCB derived cells. The UCB-MSCs differentiated poorly to adipogenic lineage compared to AF-MSCs. These results suggested that equine AF yields more MSCs with greater in vitro proliferation and differentiation capacities and is better non-invasive source of MSCs for regenerative therapies in equines.